1970
DOI: 10.1071/ea9700350
|View full text |Cite
|
Sign up to set email alerts
|

A high-yielding Mexican semi-dwarf wheat and the relationship of yield to harvest index and other varietal characteristics

Abstract: A study has been made of a Mexican semi-dwarf wheat (Lerma Rojo X Norim 10- Brevor 14) Andes3, local accession number WW 15. In 53 trials, over two seasons and a wide range of conditions, this has shown a marked grain yield superiority over other Mexican and Australian varieties when grown in high yielding environments. Nine varieties in five trials were sampled at maturity. Varietal grain yield was highly correlated with harvest index and with the number of grains set relative to straw and chaff weight. WW 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

1970
1970
1991
1991

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…Some workers reported that the yield advantage of wheat mostly depends on the higher number of grains per unit area (Gale, 1979 andPerry andD'Antuono, 1989). Furthermore, the increased grain number has been arisen by spikes per unit area (Lupton, 1974) or more grains per spike (Syme, 1970) due to a higher spikelet number (Rawson, 1970) or a higher floret fertility (Angus and Sage, 1980). Rawson and Ruwali (1972b) suggested that high yields with uniform grain can be obtained by increasing spikelet number using branched ears, rather than by increasing seed set per spikelet.…”
Section: Resultsmentioning
confidence: 99%
“…Some workers reported that the yield advantage of wheat mostly depends on the higher number of grains per unit area (Gale, 1979 andPerry andD'Antuono, 1989). Furthermore, the increased grain number has been arisen by spikes per unit area (Lupton, 1974) or more grains per spike (Syme, 1970) due to a higher spikelet number (Rawson, 1970) or a higher floret fertility (Angus and Sage, 1980). Rawson and Ruwali (1972b) suggested that high yields with uniform grain can be obtained by increasing spikelet number using branched ears, rather than by increasing seed set per spikelet.…”
Section: Resultsmentioning
confidence: 99%
“…However, as continuing competition within the crop from 3 December resulted in the reduction from 3.27 to 2.87 of grain numbers in mid-ear spikelets, it can be assumed that what appears to be the most sensitive stage of this crop, with respect to grain set, coincided with rapid ear growth and early stages of grain formation, Nitrogen fertiliser improved grain set in midear spikelets of mains terns of the semidwarf wheat 'Karamu' but not in the New Zealand cultivars (Table 3). Syme (1970) also noted that grain set in the predecessor of 'Karamu' improved with better nitrogen nutrition. Although grain set in 'Aotea' and 'Arawa' are affected by nitrogen nutrition (Langer & Hanif 1973;Langer & Liew 1973), it is apparent that the semidwarf wheats are more responsive to higher fertility than standard wheats (Syme 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Syme (1970) also noted that grain set in the predecessor of 'Karamu' improved with better nitrogen nutrition. Although grain set in 'Aotea' and 'Arawa' are affected by nitrogen nutrition (Langer & Hanif 1973;Langer & Liew 1973), it is apparent that the semidwarf wheats are more responsive to higher fertility than standard wheats (Syme 1970). Comparisons of standard New Zealand cultivars with 'Karamu' are complicated by the considerable differences in stage of development arising from the early floral initiation of the semidwarf.…”
Section: Discussionmentioning
confidence: 99%
“…When biomass differences between plots are not the result of differences in competitive ability, but of the genetical make-up oflines this correction method fails. However, there are indications that differences in biomass yield of genetical origin are relatively unimportant (SYME, 1970;AGUILAR & FISCHER, 1975;DONALD & HAMBLIN, 1976;JAIN & KUHLSHRESTHA, 1976;KRAMER, 1979).…”
Section: Selection For Wheat Yield Materials and Methodsmentioning
confidence: 99%